A comparison of silver‐ and copper‐charged polypropylene feed spacers for biofouling control. Issue 3 (30th July 2012) - Hausman, Richard; Escobar, Isabel C.
Abstract: Implementation of nanofiltration (NF) and reverse osmosis (RO) processes in treating traditional water sources can provide a steady‐state level of removal that eliminates the need for regeneration of ion exchange resins or granular activated carbon. Moreover, RO can help meet future potable water demands through desalination of seawater and brackish waters. The productivity of membrane filtration is severely lowered by fouling, which is caused by the accumulation of foreign substances on the surface and/or within pores of membranes. Microbial fouling, or biofouling, is the growth of microorganisms on the membrane surface and on the feed spacer as present between the envelopes. The fouling of membranes has demanded and continues to demand considerable attention from industry and research communities. Many of these applications use membranes in a spiral wound configuration that contains a feed spacer. The goal of this project was to develop low‐biofouling polypropylene (PP) spacers through the functionalization of PP by a spacer arm with metal chelating ligands charged with biocidal metal ions, investigate the use of this metal‐charged polypropylene (PP) feed spacers that target biofouling control, and to use some traditional and one novel techniques to autopsy the membranes after filtration to gain a better understanding of the biofouling mechanism and how the modified spacers are affecting it. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013 Abstract :